2018
DOI: 10.3390/ma11112179
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Varying Almond Shell Flour (ASF) Loading in Composites with Poly(Butylene Succinate (PBS) Matrix Compatibilized with Maleinized Linseed Oil (MLO)

Abstract: In this work poly(butylene succinate) (PBS) composites with varying loads of almond shell flour (ASF) in the 10–50 wt % were manufactured by extrusion and subsequent injection molding thus showing the feasibility of these combined manufacturing processes for composites up to 50 wt % ASF. A vegetable oil-derived compatibilizer, maleinized linseed oil (MLO), was used in PBS/ASF composites with a constant ASF to MLO (wt/wt) ratio of 10.0:1.5. Mechanical properties of PBS/ASF/MLO composites were obtained by standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 76 publications
10
30
0
Order By: Relevance
“…According to other authors, cellulose, hemicelluloses and lignin show a broad temperature range starting at about 250 • C and ending at 450 • C in a progressive weight loss process, and this degradation can reduce the thermal stability of biopolyesters [43][44][45]. Similar findings were reported by Liminana et al [31] who observed a decrease of 11.2 • C in thermal stability of PBS with the addition of 30 wt % of almond shells. The addition of MLO (Figure 5c,d) exerted a limited positive effect on the overall thermal stability of the biocomposites (Table 3).…”
Section: Morphological and Thermal Analysissupporting
confidence: 83%
See 1 more Smart Citation
“…According to other authors, cellulose, hemicelluloses and lignin show a broad temperature range starting at about 250 • C and ending at 450 • C in a progressive weight loss process, and this degradation can reduce the thermal stability of biopolyesters [43][44][45]. Similar findings were reported by Liminana et al [31] who observed a decrease of 11.2 • C in thermal stability of PBS with the addition of 30 wt % of almond shells. The addition of MLO (Figure 5c,d) exerted a limited positive effect on the overall thermal stability of the biocomposites (Table 3).…”
Section: Morphological and Thermal Analysissupporting
confidence: 83%
“…Recently, vegetable oils have been proposed as environmentally friendly compatibilizers as an alternative to conventional petroleum-based ones [29]. Specifically, maleinized linseed oil (MLO) has been used as a compatibilizer in biopolymer/ASP composites [11,30,31]. In these works, authors discussed plasticization and compatibilization effects provided by MLO due to the interaction between succinic anhydride polar groups contained in MLO and hydroxyl groups in ASP (hydroxyl groups in cellulose).…”
Section: Introductionmentioning
confidence: 99%
“…The second trend in the development of natural composites is the application of powder‐like fillers, mostly ground waste lignified parts of various plants, whose application allows to significantly reduce the final product's price . The application of ground husks, cobs, shells, and seeds has become attractive mostly due to their high local availability and low cost . It should be mentioned that apart from cost‐effectiveness, natural waste fillers may serve as modifiers of PLA matrix, with a reinforcing or plasticizing effect.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Therefore, PBS is a type of ideal plastic matrix for the preparation of biodegradable composites. 7,8 Nonetheless, natural fibers and PBS are both flammable. The environmental-friendly PBS/wood-plastic composites (WPCs) are prepared by blending PBS with wood fiber, which can effectively reduce the cost of PBS and alleviate the threat of oil crisis and white pollution.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental-friendly PBS/wood-plastic composites (WPCs) are prepared by blending PBS with wood fiber, which can effectively reduce the cost of PBS and alleviate the threat of oil crisis and white pollution. 7,8 Nonetheless, natural fibers and PBS are both flammable. 9,10 The WPC without flame retardant modification may cause serious fire safety hazard.…”
Section: Introductionmentioning
confidence: 99%